An empirical investigation between renewable energy consumption, globalization and human capital: A dynamic auto-regressive distributive lag simulation - Ozcan, Burcu; Danish; Temiz, Mehmet (Pergamon-Elsevier Science Ltd, 2022)
This study analyzes the dynamic effects of overall globalization and its three sub-dimensions (economic globalization, political globalization, and social globalization) on renewable energy consumption in Turkey using annual data from 1980 to 2017. As an estimation technique, the dynamic autoregressive distributed lag simulation (dynamic ARDL) developed by Jordan and Philips (2018) is employed. The results indicate that the overall globalization process, both in the short-run and in the long run, and its dimensions of economic and political globalization, only in the long-run, have positive and significant effects on Turkey's renewable energy consumption. However, social globalization does not have any significant effect on renewable energy consumption either in the short-run and in the long run. Additionally, increases in Turkey's human capital stock and economic growth rate appear to cause more renewable energy consumption. Based on those results, some important policy implications encouraging the globalization and economic growth processes and enriching the human capita stock are suggested. (c) 2022 Elsevier Ltd.
Keywords: Renewable energy consumption; Globalization; Human capital; Turkey; Dynamic ARDL